FEATURES OF THE POSTOPERATIVE PERIOD FOR MENINGIOMA OF THE SKULL BASE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
work There was a study of the clinical and morphological signs of the brain tumor, identificationof prognostically significant factors among them, analysis of the results of surgical treatment andthe development of rational treatment tactics for these brain tumors.